Hard coating film, and window and image display device using same
By forming a hard coat film composed of silane or siloxane compounds and fluorine-containing UV curable functional group compounds on the display glass, the problem of fragments scattering when the flexible display glass is broken is solved, and high durability and anti-scattering effect are achieved.
Patent Information
- Application Number
- CN202380050888.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-30
- Filing Date
- 2023-05-30
- Publication Date
- 2025-03-07
AI Technical Summary
Existing flexible displays are prone to cracking of outer cover glass when they are frequently folded or impacted, causing glass fragments to scatter, affecting the quality and safety of the equipment.
A hard coat film is used, which consists of a first hard coat layer and a second hard coat layer. The first hard coating layer contains a silane or a siloxane compound, with a Vickers hardness of less than 20 kgf/mm2; the second hard coating layer contains a compound containing a fluorine-based UV curing functional group, with a thickness of 3 to 15 μm.
It is realized that glass fragments are prevented from scattering during breakage, and the scratch resistance, stain resistance, wear resistance, reagent resistance, press resistance, scatter resistance, adhesion and bending properties of the window and image display device are improved, and the production process is simplified.
Smart Images

Figure CN119585221A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a hard coating film and a window and an image display device using the hard coating film. Background Art
[0002] In recent years, image display devices such as liquid crystal display (LCD) devices and organic light emitting display (OLED) devices have continued to become thinner and more flexible. Such image display devices are widely used in various smart devices characterized by portability, such as smart phones, tablet PCs, and various wearable devices. In such flexible displays, a glass substrate layer with physical properties such as high transparency, hardness, and bending characteristics is required.
[0003] On the other hand, when flexible displays are folded frequently or subjected to impacts beyond the limit, the outer glass often breaks. In this case, small pieces of glass may fly around in large quantities, which may cause quality problems such as foreign matter on the display and device surface, and may also cause safety accidents. In order to prevent this from happening and ensure the stability of glass fragments when broken, anti-scattering films are sometimes included in the window layer.
[0004] Korean Patent Registration No. 10-1408511 provides a transparent substrate having excellent bendability and flexibility, which significantly prevents crack propagation and breakage of the thin glass by reinforcing the thin glass by providing a resin layer having a specific shrinkage stress on one or both sides of the thin glass.
[0005] However, in order to form the resin layer, it is necessary to arrange it on one or both surfaces of the sheet glass with an adhesive layer interposed therebetween, which causes a problem that the production process of the substrate becomes complicated.
[0006] Therefore, the actual situation is that it is necessary to develop a hard coating film that simplifies the process by directly forming a base material layer for preventing scattering on glass, has excellent adhesion, and has durability suitable for achieving flexible characteristics. Summary of the invention
[0007] Technical issues
[0008] In order to solve the above-mentioned problems, an object of the present invention is to provide a hard coating film having excellent quality and preventing fragments from scattering when broken.
[0009] Specifically, the object is to provide a window and an image display device having high hardness and excellent scratch resistance, antifouling property, abrasion resistance, chemical resistance, pressure resistance, anti-scattering property, adhesion and bendability when the hard coating film is applied.
[0010] However, the problems to be solved by the present invention are not limited to the problems mentioned above, and a person skilled in the art should be able to understand other problems not mentioned based on the following description.
[0011] Solution to the problem
[0012] In order to achieve the above technical problem, the present invention provides a hard coating film for forming on a display glass, characterized in that it comprises: a first hard coating layer comprising a silane or siloxane compound and having a Vickers hardness of 20 kgf / mm 2 and a second hard coating layer formed on the first hard coating layer, comprising a compound containing a fluorine-based UV-curable functional group and having a thickness of 3 to 15 μm.
[0013] In the present invention, the display glass may be ultra-thin glass (Ultra Thin Glass, UTG).
[0014] In the present invention, the glass for a display, the first hard coating layer, and the second hard coating layer may be formed in direct contact with each other without including any other layer.
[0015] In the present invention, the fluorine-based UV-curable functional group-containing compound may have 1 to 6 UV-curable functional groups.
[0016] In the present invention, any one of the first hard coating layer and the second hard coating layer may be produced from a composition containing one or more selected from the group consisting of a photopolymerizable compound, an initiator, and a solvent.
[0017] In the present invention, the photopolymerizable compound may further contain an inorganic nanofiller.
[0018] In the present invention, any one of the first hard coating layer and the second hard coating layer may further contain an additive.
[0019] In the present invention, the additive may include at least one selected from the group consisting of a leveling agent, a UV stabilizer, and a heat stabilizer.
[0020] The present invention can be applied to flexible displays.
[0021] Furthermore, the present invention relates to a window including display glass and the hard coating film formed on the display glass.
[0022] In addition, the present invention relates to an image display device comprising the above-mentioned window.
[0023] Effects of the Invention
[0024] The hard coating film of the present invention and the window and image display device using the same have a pencil hardness of 3H or above, and are excellent in scratch resistance, anti-fouling, wear resistance, chemical resistance, pressure resistance, anti-scattering, adhesion and bendability, and can improve device reliability when applied to flexible displays.
[0025] Furthermore, the hard coat film of the present invention does not include an additional substrate between the glass and the hard coat layer, but is formed in direct contact with the glass and the hard coat layer, so that the step of bonding the substrate layers can be omitted, and the production process can be simplified compared with the related art. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] Figure 1 The diagram shows a laminated structure of a display glass laminated with a hard coating film according to one embodiment of the present invention.
[0027] The meanings of the symbols in the figure are as follows:
[0028] 100: laminated body,
[0029] 110: Display glass,
[0030] 120a: first hard coating layer,
[0031] 120b: Second hard coating layer. DETAILED DESCRIPTION
[0032] The present invention relates to a hard coating film suitable for a flexible display, and a window and an image display device using the same. The hard coating film is used to be formed on the above-mentioned display glass, and comprises: a first hard coating layer, which comprises a silane or siloxane compound and has a Vickers hardness of 20 kgf / mm 2 and a second hard coating layer formed on the first hard coating layer, comprising a compound containing a fluorine-based UV-curable functional group and having a thickness of 3 to 15 μm.
[0033] Hereinafter, preferred embodiments of the present invention will be described in detail. However, these embodiments are provided for the purpose of illustrating the present invention in more detail, and it is obvious to a person skilled in the art that the scope of the present invention is not limited by these embodiments.
[0034] The terms used in this specification are intended to illustrate the embodiments and are not intended to limit the present invention. In this specification, unless otherwise specifically mentioned in the context, the singular form also includes the plural form. For example, the "hard coating" used in this specification may refer to at least one of the first hard coating and the second hard coating.
[0035] The terms "comprises" and / or "comprising" used in this specification are used to mean that they do not exclude the existence or addition of one or more other constituent elements, steps, operations and / or elements other than the mentioned constituent elements, steps, operations and / or elements. Throughout the specification, the same reference numerals refer to the same constituent elements.
[0036] The term “substantially” used in this specification may be interpreted not only as physically identical or identical but also as including the case where the error range is within the measurement or manufacturing process, for example, the case where the error range is less than 0.1%.
[0037] Figure 1 FIG. 4 shows a laminated structure of a display glass laminated with a hard coating film according to an embodiment of the present invention. Figure 1 As shown, the laminated body 100 of the present invention may include a display glass 110, a first hard coating layer 120a formed on the display glass 110, and a second hard coating layer 120b formed on the first hard coating layer, that is, as an outermost layer.
[0038] The hard coating film of the present invention can have both hardness and flexibility to be applied to a window for a flexible display.
[0039] <Display Glass (110)>
[0040] The display glass is intended to replace the conventional glass substrate to support the hard coating layer 120 and other substrates or panels described later, and can be made of thin glass or curved glass for the display of electronic devices. The thin glass can include flat glass and flexible glass.
[0041] According to an embodiment of the present invention, the display glass 110 may be ultra-thin glass (UTG). Ultra-thin glass (UTG) is a component of ultra-thin tempered glass material used for display outer cover windows, and has the characteristics of high transparency, a thickness as thin as about 10 to 100 μm, and flexible foldability.
[0042] In the present invention, the term "transparent" means that the transmittance of visible light is 70% or more or 80% or more, but the present invention is not limited thereto.
[0043] The display glass 110 may include an additional substrate layer such as the hard coating layer 120 described later to ensure durability. Generally, an adhesive layer or a sticking layer is included to form or bond the substrate layer, but the hard coating film according to the present invention is characterized in that it is formed in direct contact without including an additional substrate layer for bonding the hard coating layer, thereby simplifying the production process compared to conventional laminates.
[0044] <Hard Coat>
[0045] The hard coating film of the present invention includes a hard coating layer, and preferably may include a first hard coating layer and a second hard coating layer. In more detail, the hard coating film of the present invention is formed on a display glass, and may include: a first hard coating layer, which includes a silane or siloxane compound and has a Vickers hardness of 20 kgf / mm 2 and a second hard coating layer formed on the first hard coating layer, comprising a compound containing a fluorine-based UV-curable functional group and having a thickness of 3 to 15 μm.
[0046] Hard coating 120
[0047] like Figure 1 As shown, the hard coating layer of the present invention may include a first hard coating layer 120a and a second hard coating layer 120b.
[0048] According to one embodiment of the present invention, the first hard coating layer 120a is characterized by comprising a silane or siloxane compound and having a Vickers hardness of 20 kgf / mm 2 Hereinafter, the Vickers hardness satisfies the above range, thereby preventing fragments from flying when the window is broken. In addition, the second hard coating layer 120b is exposed on the surface, giving antifouling properties and protecting the film. The second hard coating layer 120b is characterized in that it contains a compound containing a fluorine-based UV curable functional group and has a thickness of 3 to 15 μm.
[0049] Reference Figure 1 The first hard coating layer 120a may be formed on the display glass 110, and the second hard coating layer 120b may be formed on the first hard coating layer 120a, i.e., the outermost layer of the hard coating film. The first hard coating layer 120a ensures adhesion between substrates and imparts impact resistance even without an additional substrate layer such as an adhesive layer.
[0050] According to an embodiment of the present invention, as described above, the display glass 110 may be ultra thin glass (UTG), and the display glass 110 , the first hard coating layer 120 a , and the second hard coating layer 120 b may be formed in direct contact with each other without including additional layers.
[0051] In addition, the first hard coating layer 120a and the second hard coating layer 120b can be independently manufactured from a hard coating composition comprising one or more selected from the group consisting of a photopolymerizable compound, a solvent and an initiator, and the composition can also contain one or more selected from the group consisting of a leveling agent, a UV stabilizer and a heat stabilizer as an additive as needed. As an example, the first hard coating layer can be manufactured from a hard coating composition comprising a silane or siloxane compound, a photopolymerizable compound, an initiator and a solvent.
[0052] In addition, the second hard coating layer can be produced from a hard coating composition containing a compound having a fluorine-based UV-curable functional group, a photopolymerizable compound, an initiator, and a solvent.
[0053] Silane or siloxane compounds
[0054] The above-mentioned siloxane compound contained in the first hard coating layer 120a of the present invention includes a compound having a Si-O-Si bond. In the present invention, the Si-O bonding force of the above-mentioned siloxane compound is stronger than that of the CC bond, which not only has excellent impact resistance, but also can impart excellent adhesion to other adjacent substrates. In addition, the Si-O bond length is longer than CC, and the bond angle of Si-O-Si is 143°, which is also larger than the bond angle of 110° of the CCC bond, so it has excellent flexibility to resist deformation. Therefore, the silane or siloxane compound of the present invention has an excellent elastic recovery rate compared with carbon materials. The above-mentioned siloxane compound can be in the form of -(R2SiO)- with two organic groups bonded to the silicon element or -(RSiO 1.5 )-form. Examples of -(R2SiO)-form include polydimethylsiloxane (PDMS) and the like. 1.5 Examples of the silsesquioxane-type include cage silsesquioxane, partial cage silsesquioxane, ladder silsesquioxane, random silsesquioxane, etc. The organic group may have a photocurable (meth)acryloyl functional group or epoxy functional group.
[0055] The above-mentioned silane compound includes a compound having an X-Si-(OR)3 bond, but is not limited thereto. As an example, a silane coupling agent can be cited as an example of an X-Si-(OR)3 type. X of the above-mentioned silane compound is a reactive group that forms a chemical bond with an organic material, and may have a photocurable (meth)acryloyl functional group or epoxy functional group. R of the above-mentioned silane or siloxane compound refers to an arbitrary organic group, and includes, without limitation, the organic groups of known silane or siloxane compounds.
[0056] According to one embodiment of the present invention, the content of the silane or siloxane compound can be 1 to 10 parts by weight, preferably 3 to 10 parts by weight, relative to 100 parts by weight of the hard coating composition. By including the silane or siloxane compound in the above range, the hard coating layer formed by the hard coating composition has good adhesion to the substrate, can provide flexibility to the film substrate layer, and can prevent broken fragments from scattering when damaged due to frequent folding or external impact.
[0057] Compounds containing fluorine-based UV-curable functional groups
[0058] The compound containing a fluorine-based UV-curable functional group contained in the second hard coating layer 120 b of the present invention is a component that imparts antifouling properties and abrasion resistance, and is not particularly limited as long as it contains fluorine and has a UV-curable functional group.
[0059] Specifically, acrylates, methacrylates, vinyls, etc. containing perfluorinated groups can be used. At this time, the compound containing a fluorinated UV-curable functional group preferably has 1 to 6 UV-curable functional groups, but the scope of the present invention is not limited thereto, and any substance having a UV-curable functional group and containing a fluorinated group can be used.
[0060] The amount of the hard coating composition is preferably 0.01 to 30 parts by weight relative to 100 parts by weight of the total hard coating composition. If the amount is less than 0.01 parts by weight, it is difficult to achieve sufficient wear resistance and antifouling properties, and if the amount is greater than 30 parts by weight, not only the film hardness, but also the wear resistance may be reduced.
[0061] Photopolymerizable compounds
[0062] The photopolymerizable compound used for forming the hard coat layer of the present invention is a compound containing a photopolymerizable functional group, and may be a photopolymerizable monomer, a photopolymerizable oligomer, or the like, and may be, for example, a photoradical polymerizable compound.
[0063] The photopolymerizable monomers may be any monomers used in the art that have unsaturated groups such as (meth)acryloyl, vinyl, styryl, and allyl groups in the molecule as photocurable functional groups. More specifically, for example, monofunctional and / or multifunctional (meth)acrylates may be used alone or in combination of two or more.
[0064] In the present invention, "(meth)acryloyl-" means "methacryloyl-", "acryloyl-" or both.
[0065] Specific examples of the (meth)acrylate monomer include: (meth)acrylates such as trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, glycerol tri(meth)acrylate, tri(2-hydroxyethyl)isocyanurate tri(meth)acrylate, ethylene glycol di(meth)acrylate, propylene glycol (meth)acrylate, 1,3-butanediol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, neopentyl glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, dipropylene glycol di(meth)acrylate, bis(2-hydroxyethyl)isocyanurate di(meth)acrylate, and poly(meth)acrylates obtained by adding ethylene oxide or propylene oxide to the above (meth)acrylates; Oligomeric ester (meth)acrylates, oligomeric ether (meth)acrylates, oligomeric urethane (meth)acrylates and oligomeric epoxy (meth)acrylates having 1 to 3 (meth)acryloyl groups in the (meth)acrylate; hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, hydroxybutyl (meth)acrylate and products obtained by adding ethylene oxide or propylene oxide to the above (meth)acrylates; and monomers having trifunctional or less (meth)acryloyl groups such as mono(meth)acrylate, isooctyl (meth)acrylate, isodecyl (meth)acrylate, stearyl (meth)acrylate, tetrahydrofurfuryl (meth)acrylate and phenoxyethyl (meth)acrylate; and dipentaerythritol hexa(meth)acrylate, dipentaerythritol hydroxypenta(meth)acrylate, pentaerythritol tetra(meth)acrylate, ditrimethylolpropane tetra(meth)acrylate and the like. These can be used alone or in combination of two or more.
[0066] The photopolymerizable oligomer may be, for example, one or more selected from the group consisting of epoxy (meth)acrylate, urethane (meth)acrylate, and polyester (meth)acrylate. Specifically, urethane (meth)acrylate and polyester (meth)acrylate may be mixed for use, or two polyester (meth)acrylates may be mixed for use. In order to improve the scratch resistance and hardness of the cured product and increase the elastic modulus of the hard coating, it is preferred to include a urethane (meth)acrylate oligomer.
[0067] The urethane (meth)acrylate can be produced by reacting a polyfunctional (meth)acrylate having a hydroxyl group in the molecule with a compound having an isocyanate group in the presence of a catalyst according to a method known in the art.
[0068] Specific examples of the multifunctional (meth)acrylate having a hydroxyl group in the molecule may be one or more selected from the group consisting of 2-hydroxyethyl (meth)acrylate, 2-hydroxyisopropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, caprolactone ring-opening hydroxy acrylate, a pentaerythritol tri / tetra(meth)acrylate mixture, and a dipentaerythritol penta / hexa(meth)acrylate mixture.
[0069] Specific examples of the compound having an isocyanate group include a compound selected from the group consisting of 1,4-diisocyanatobutane, 1,6-diisocyanatohexane, 1,8-diisocyanatooctane, 1,12-diisocyanatododecane, 1,5-diisocyanato-2-methylpentane, trimethyl-1,6-diisocyanatohexane, 1,3-bis(isocyanatomethyl)cyclohexane, trans-1,4-cyclohexene diisocyanate, 4,4′-methylenebis(cyclohexyl isocyanate), isocyanate, and isocyanate. One or more selected from the group consisting of phorone diisocyanate, toluene-2,4-diisocyanate, toluene-2,6-diisocyanate, xylene-1,4-diisocyanate, tetramethylxylene-1,3-diisocyanate, 1-chloromethyl-2,4-diisocyanate, 4,4'-methylenebis(2,6-dimethylphenylisocyanate), 4,4'-oxybis(phenylisocyanate), trifunctional isocyanates of hexamethylene diisocyanate, and trimethylene propanol-added toluene diisocyanate.
[0070] More specifically, the urethane (meth)acrylate oligomer may be a compound including two or more substituents represented by the following Chemical Formula 1 and a (meth)acryloyl group, respectively, in a molecule.
[0071] [Chemical formula 1]
[0072] *-OC(=O)NH-*
[0073] The urethane (meth)acrylate oligomer may be produced by reacting 1 mol of a diisocyanate represented by the following Chemical Formula 2 with 2 mol of a polymerizable unsaturated compound containing active hydrogen.
[0074] [Chemical formula 2]
[0075] R1-OC(=O)NH-R3-NHC(=O)O-R2
[0076] In the formula, R1 and R2 are each independently a (meth)acryloyl-containing substituent derived from an active hydrogen-containing polymerizable unsaturated compound, and R3 is a divalent substituent derived from a diisocyanate.
[0077] Specific examples of the urethane (meth)acrylate oligomer include products obtained by the reaction of 2-hydroxyethyl (meth)acrylate and 2,4-toluene diisocyanate, the reaction of 2-hydroxyethyl (meth)acrylate and isophorone diisocyanate, the reaction of 2-hydroxybutyl (meth)acrylate and 2,4-toluene diisocyanate, the reaction of 2-hydroxybutyl (meth)acrylate and isophorone diisocyanate, the reaction of pentaerythritol tri(meth)acrylate and 2,4-toluene diisocyanate, the reaction of pentaerythritol tri(meth)acrylate and isophorone diisocyanate, the reaction of pentaerythritol tri(meth)acrylate and dicyclohexylmethane diisocyanate, the reaction of dipentaerythritol penta(meth)acrylate and isophorone diisocyanate, and the reaction of dipentaerythritol penta(meth)acrylate and dicyclohexylmethane diisocyanate.
[0078] Polyester (meth)acrylate can be produced by reacting polyester polyol with acrylic acid according to a method known in the art.
[0079] The polyester (meth)acrylate may be, for example, one or more selected from the group consisting of polyester acrylate, polyester diacrylate, polyester tetraacrylate, polyester hexaacrylate, polyester pentaerythritol triacrylate, polyester pentaerythritol tetraacrylate, and polyester pentaerythritol hexaacrylate, but is not limited thereto.
[0080] The photopolymerizable monomer and the photopolymerizable oligomer may be used alone or in combination. When the photopolymerizable monomer and the photopolymerizable oligomer are used in combination, the handling properties and compatibility of the hard coating composition can be improved.
[0081] The content ratio of the photopolymerizable monomer to the photopolymerizable oligomer is not particularly limited, and can be appropriately selected in consideration of the storage modulus, shrinkage force, and operability of the hard coat layer, for example, the content ratio of the polymerizable oligomer to the polymerizable monomer can be a ratio of (1:10) to (10:1). When the content ratio of the polymerizable oligomer to the polymerizable monomer deviates from the above range, the storage modulus of the hard coat layer decreases or the shrinkage force increases, while the hardness and flexibility decrease, and curling may occur.
[0082] The content of the photopolymerizable compound is not particularly limited, and for example, the content may be 1 to 80 parts by weight, preferably 5 to 50 parts by weight, relative to 100 parts by weight of the hard coating composition. If the content of the photopolymerizable compound is less than 1 part by weight, the elastic modulus of the hard coating layer decreases and cracks may easily occur in the hard coating layer when bent, and if the content is greater than 80 parts by weight, the viscosity increases and the coating property deteriorates, and the surface leveling may be insufficient, causing problems in appearance characteristics.
[0083] The above-mentioned photopolymerizable compound can be used together with an inorganic nanofiller to improve hardness and scratch resistance. The above-mentioned inorganic nanofiller can generally use a nanofiller of less than 100 nm, preferably 10 to 100 nm, and more preferably 10 to 50 nm. As a representative inorganic nanofiller, for example, silicon dioxide, aluminum oxide particles, titanium oxide particles or zinc oxide particles can be used, and silicon dioxide can be preferably used. The surface of silicon dioxide may or may not have a photocurable group that can participate in the photoreaction.
[0084] The inorganic nanofiller may be added by appropriately adjusting the content within a range that does not impair the effects of the present invention.
[0085] Solvents
[0086] The solvent is a substance capable of dissolving or dispersing the above-mentioned components, and any solvent known as a solvent for a coating layer-forming composition in the art can be used without limitation.
[0087] As the solvent that can be used, preferably alcohols (methanol, ethanol, isopropanol, butanol, methyl cellosolve, ethyl cellosolve, etc.), ketones (methyl ethyl ketone, methyl butyl ketone, methyl isobutyl ketone, diethyl ketone, dipropyl ketone, cyclohexanone, etc.), acetates (ethyl acetate, propyl acetate, n-butyl acetate, tert-butyl acetate, methyl cellosolve acetate, ethyl cellosolve acetate, propylene glycol monomethyl ether acetate, propylene glycol monoethyl ether acetate, propylene glycol monopropyl ether acetate, methoxybutyl acetate, methoxypentyl acetate, etc.), hexanes (hexane, heptane, octane, etc.), benzenes (benzene, toluene, xylene, etc.), ethers (diethylene glycol dimethyl ether, diethylene glycol diethyl ether, diethylene glycol dipropyl ether, diethylene glycol dibutyl ether, propylene glycol monomethyl ether, etc.), etc. can be used. The above-exemplified solvents can be used alone or in combination of two or more.
[0088] The solvent is used in an amount of 10 to 95 parts by weight relative to 100 parts by weight of the entire hard coating composition. If the content of the solvent is lower than the above content, the viscosity is high and the workability is poor. In addition, the swelling of the substrate film may not be sufficiently performed. On the contrary, if the content is higher than the above range, the drying process takes a long time and the economic efficiency is poor. Therefore, it is appropriately used within the above range.
[0089] Initiator
[0090] The above-mentioned initiator can be used without limitation as long as it is an initiator used in the technical field. For example, one or more selected from the group consisting of hydroxyketones, aminoketones, hydrogen abstraction type photoinitiators and combinations thereof can be used.
[0091] Specifically, as the above-mentioned photoinitiator, one or more selected from the group consisting of 2-methyl-1-[4-(methylthio)phenyl]2-morpholinoacetone-1, diphenyl ketone, benzyl dimethyl ketal, 2-hydroxy-2-methyl-1-phenyl-1-ketone, 4-hydroxycyclophenyl ketone, 2,2-dimethoxy-2-phenyl-acetophenone, anthraquinone, fluorene, triphenylamine, carbazole, 3-methylacetophenone, 4-chloroacetophenone, 4,4-dimethoxyacetophenone, 4,4-diaminobenzophenone, 1-hydroxycyclohexyl phenyl ketone, benzophenone, diphenyl (2,4,6-trimethylbenzoyl) phosphine oxide and combinations thereof can be used.
[0092] Such a photoinitiator is used in an amount of 0.1 to 10 parts by weight, preferably 1 to 5 parts by weight, relative to 100 parts by weight of the entire hard coating composition. If the content is below the above range, the curing speed of the composition may be slow and non-curing may occur, resulting in deterioration of mechanical properties. On the contrary, if the content is above the above range, cracks may be generated in the coating film due to over-curing.
[0093] additive
[0094] Furthermore, the hard coating composition used for forming the hard coating layer of the present invention may further contain additives such as a leveling agent, a UV stabilizer, and / or a heat stabilizer.
[0095] The leveling agent is a component that imparts smoothness and coating properties to the coating film. The leveling agent may be a leveling agent commonly used in the art, for example, a silicone leveling agent, a fluorine leveling agent, an acrylic polymer leveling agent, etc. These may be used alone or in combination of two or more, but are not necessarily limited thereto.
[0096] The content of the leveling agent may be 0.1 to 1 part by weight relative to 100 parts by weight of the hard coating composition, but is not limited thereto.
[0097] UV stabilizers are components that block or absorb UV rays and prevent the cured hard coating from decomposing, changing color, or breaking due to exposure to UV rays. The above-mentioned UV stabilizers can be absorbers, quenchers, hindered amine light stabilizers (HALS, Hindered Amine Light Stabilizer), etc., which are classified according to the mechanism of action; or phenyl salicylate (Phenyl Salicylates, absorbers), benzophenone (Benzophenone, absorbers), benzotriazole (Benzotriazole, absorbers), nickel derivatives (quenchers), free radical scavengers (Radical Scavengers); etc., which are classified according to the chemical structure. They can be used alone or in combination of two or more, and their types are not particularly limited, as long as they are UV stabilizers that do not significantly change the initial color of the hard coating.
[0098] As the heat stabilizer, for example, polyphenols as primary heat stabilizers, phosphate esters and lactones as secondary heat stabilizers, which are commercially available products, can be used alone or in combination.
[0099] The above-mentioned ultraviolet stabilizer and heat stabilizer can be used in an appropriately adjusted content at a level that does not affect ultraviolet curability. Specifically, the content thereof is preferably 0.1 to 3 parts by weight based on 100 parts by weight of the total hard coating composition of the present invention.
[0100] The above-mentioned additives can be added by appropriately adjusting the content within a range that does not impair the effects of the present invention.
[0101] The hard coating layer can be manufactured by a method known in the art. The thickness of the first hard coating layer is not particularly limited, for example, it can be 5 to 100 μm, and the thickness of the second hard coating layer can be 3 to 15 μm, preferably 5 to 10 μm. If the thickness is within the above range, it can show better hardness and flexibility.
[0102] The hard coating film of the embodiment of the present invention can form a first hard coating layer 120a by applying a first hard coating composition on a display glass 110 and performing drying and UV curing steps, and then a second hard coating layer 120b can be formed by applying a second hard coating composition on the first hard coating layer 120a and performing drying and UV curing steps in the same manner as the first hard coating layer.
[0103] The step of drying the hard coating film may be performed using a heating tool such as a hot plate, a hot air circulation oven, an infrared oven, etc., and may be performed at a temperature of 50 to 150°C or 50 to 100°C.
[0104] In the step of curing the hard coating film, 50 to 1000 mJ / cm 2 , preferably 200 to 800 mJ / cm 2 In particular, the first hard coating layer 120a may be formed by applying 50 to 600 mJ / cm 2 The primary curing is performed weakly at a level and 300 to 800 mJ / cm 2 The second hard coating layer and the first hard coating layer are further enhanced by irradiating with strong light of UV. As the light source used in the irradiation, a low-pressure mercury lamp, a high-pressure mercury lamp, an ultra-high-pressure mercury lamp, a metal halide lamp, an argon laser, etc. can be used, and X-rays, electron beams, etc. can also be used as needed.
[0105] <Window and Image Display Device>
[0106] Embodiments of the present invention provide a window and an image display device including the display glass and a hard coating film.
[0107] For example, the hard coating film or the laminate containing the hard coating film can be used as a window or a window laminate, and at least one of a polarizing layer or a touch sensor layer can be laminated on one side of the window formed with the hard coating film. Such a window or a window laminate can be used as a window film formed on the outermost surface of an image display device. In addition, the hard coating film can also be inserted into, for example, an image display device.
[0108] The above-mentioned image display device includes various image display devices such as liquid crystal display device, electroluminescent display device, plasma display device, field emission display device, etc., and can be a flexible display device with flexibility and bending characteristics.
[0109] In this case, the hard coating stack of the embodiment of the present invention can be more effectively used as the window or window stack of the above-mentioned flexible display device. Through the interaction between the substrate layer and the easy-adhesion layer contained in the hard coating film of the embodiment of the present invention, the flexibility and durability of the window can be improved at the same time, and the antistatic performance can also be achieved together. Thus, for example, the impact resistance and wear resistance of the above-mentioned flexible display device can be improved, and damage such as cracks and peeling can also be prevented when bending or folding (bending).
[0110] Implementation
[0111] The following are specific examples of the present invention. However, the present invention is not limited to the following examples, and can be implemented in various different ways. The examples are provided only to make the disclosure of the present invention complete and to fully inform the general technicians of the technical field to which the present invention belongs of the scope of the invention. The present invention is defined only by the scope of the claims. Unless otherwise stated, "%" and "parts" are mass % and mass parts, respectively.
[0112] Production Example: Production of Hard Coat Composition
[0113] Production Example 1
[0114] 5 parts by weight of tetradecafunctional acrylate (VISCOAT#1000, Osaka Organic Chemical Co., Ltd.), 43 parts by weight of hexafunctional urethane acrylate (U-6LPA, Shin-Nakamura Chemical Co., Ltd.), 1 part by weight of 1-hydroxycyclohexyl phenyl ketone, 1 part by weight of a fluorine-containing UV-curable functional group compound (KY-1203, Shin-Etsu Co., Ltd.), and 50 parts by weight of methyl ethyl ketone were mixed using a stirrer and then filtered using a PP filter to prepare a second hard coating composition.
[0115] Production Example 2
[0116] 5 parts by weight of tetradecafunctional acrylate (VISCOAT#1000, Osaka Organic Chemical Co., Ltd.), 43 parts by weight of hexafunctional urethane acrylate (U-6LPA, Shin-Nakamura Chemical Co., Ltd.), 1 part by weight of 1-hydroxycyclohexyl phenyl ketone, 1 part by weight of a fluorine-containing UV-curable functional group compound (FS-7026, Fluoro Technology Co., Ltd.), and 50 parts by weight of methyl ethyl ketone were mixed using a stirrer and then filtered using a PP filter to prepare a second hard coating composition.
[0117] Production Example 3
[0118] 44 parts by weight of a difunctional acrylate (UA5216 from Amerigen Specialty Chemicals), 0.5 parts by weight of 1-hydroxycyclohexyl phenyl ketone, 0.5 parts by weight of a silicone additive (BYK, BYK-UV3530), 50 parts by weight of methyl ethyl ketone, and 5 parts by weight of an acrylic silane compound (KR-513 from Shin-Etsu Silicone Co., Ltd.) were mixed using a stirrer and then filtered using a PP filter to prepare a first hard coating composition.
[0119] Production Example 4
[0120] 40 parts by weight of a difunctional acrylate (UA5216 from Miyuan Specialty Chemicals), 4 parts by weight of a tetradecafunctional acrylate (VISCOAT#1000 from Osaka Organic Chemicals), 0.5 parts by weight of 1-hydroxycyclohexyl phenyl ketone, 0.5 parts by weight of a silicone additive (BYK-UV3530 from BYK), 50 parts by weight of methyl ethyl ketone, and 5 parts by weight of an acrylic silane compound (KBM-5803 from Shin-Etsu Silicone Co., Ltd.) were mixed using a stirrer and then filtered using a PP filter to prepare a first hard coating composition.
[0121] Production Example 5
[0122] 33 parts by weight of a difunctional acrylate (UA5216 from Miyuan Specialty Chemicals), 11 parts by weight of a tetradecafunctional acrylate (VISCOAT#1000 from Osaka Organic Chemicals), 0.5 parts by weight of 1-hydroxycyclohexyl phenyl ketone, 0.5 parts by weight of a silicone additive (BYK-UV3530 from BYK), 50 parts by weight of methyl ethyl ketone, and 5 parts by weight of an acrylic silane compound (KBM-503 from Shin-Etsu Silicone Co., Ltd.) were mixed using a stirrer and then filtered using a PP filter to prepare a first hard coating composition.
[0123] Production Example 6
[0124] 22 parts by weight of a difunctional acrylate (UA5216 from Miyuan Specialty Chemicals), 22 parts by weight of a tetradecafunctional acrylate (VISCOAT#1000 from Osaka Organic Chemicals), 0.5 parts by weight of 1-hydroxycyclohexyl phenyl ketone, 0.5 parts by weight of a silicone additive (BYK-UV3530 from BYK), 50 parts by weight of methyl ethyl ketone, and 5 parts by weight of an acrylic silane compound (KBM-5803 from Shin-Etsu Silicone Co., Ltd.) were mixed using a stirrer and then filtered using a PP filter to prepare a first hard coating composition.
[0125] Production Example 7
[0126] 11 parts by weight of a difunctional acrylate (UA5216 from Miyuan Specialty Chemicals), 33 parts by weight of a tetradecafunctional acrylate (VISCOAT#1000 from Osaka Organic Chemicals), 0.5 parts by weight of 1-hydroxycyclohexyl phenyl ketone, 0.5 parts by weight of a silicone additive (BYK-UV3530 from BYK), 50 parts by weight of methyl ethyl ketone, and 5 parts by weight of an acrylic silane compound (KBM-503 from Shin-Etsu Silicone Co., Ltd.) were mixed using a stirrer and then filtered using a PP filter to prepare a first hard coating composition.
[0127] Production Example 8
[0128] 44 parts by weight of tetradecafunctional acrylate (VISCOAT#1000, Osaka Organic Chemical Co., Ltd.), 0.5 parts by weight of 1-hydroxycyclohexyl phenyl ketone, 0.5 parts by weight of silicone additive (BYK-UV3530, BYK-UV3530), 50 parts by weight of methyl ethyl ketone, and 5 parts by weight of acrylic silane compound (KR-513, Shin-Etsu Silicone Co., Ltd.) were mixed with a stirrer and then filtered with a PP filter to prepare a first hard coating composition.
[0129] Production Example 9
[0130] 21.75 parts by weight of difunctional acrylate (UA5216, U.S. Chemicals, Inc.), 21.75 parts by weight of tetradecafunctional acrylate (VISCOAT#1000, Osaka Organic Chemical Co., Ltd.), 0.5 parts by weight of 1-hydroxycyclohexyl phenyl ketone, 0.5 parts by weight of cationic initiator (Omnirad-250, IGM), 0.5 parts by weight of silicone additive (BYK-UV3530, BYK-UV3530, BYK-UV3530, BYK-UV3530, 50 parts by weight of methyl ethyl ketone, and 5 parts by weight of acrylic siloxane compound (ASO-101, Sooyangchemtec) were mixed with a stirrer and then filtered with a PP filter to prepare a first hard coating composition.
[0131] Production Example 10
[0132] 21.75 parts by weight of difunctional acrylate (UA5216 from Amerigen Specialty Chemicals), 21.75 parts by weight of tetradecafunctional acrylate (VISCOAT#1000 from Osaka Organic Chemicals), 0.5 parts by weight of 1-hydroxycyclohexyl phenyl ketone, 0.5 parts by weight of cationic initiator (Omnirad-250 from IGM), 0.5 parts by weight of silicone additive (BYK-UV3530 from BYK), 50 parts by weight of methyl ethyl ketone, and 5 parts by weight of epoxy silane compound (KR-517 from Shin-Etsu Silicone Co., Ltd.) were mixed using a stirrer and then filtered using a PP filter to prepare a first hard coating composition.
[0133] Production Example 11
[0134] 5 parts by weight of tetradecafunctional acrylate (VISCOAT#1000, Osaka Organic Chemical Co., Ltd.), 43 parts by weight of hexafunctional urethane acrylate (U-6LPA, Shin-Nakamura Chemical Co., Ltd.), 1 part by weight of 1-hydroxycyclohexyl phenyl ketone, 1 part by weight of silicone additive (BYK, BYK-307), and 50 parts by weight of methyl ethyl ketone were mixed with a stirrer and then filtered with a PP filter to prepare a second hard coating composition.
[0135] Production Example 12
[0136] 24.5 parts by weight of difunctional acrylate (UA5216, Amerigen Specialty Chemicals), 24.5 parts by weight of tetradecafunctional acrylate (VISCOAT#1000, Osaka Organic Chemicals), 0.5 parts by weight of 1-hydroxycyclohexyl phenyl ketone, 0.5 parts by weight of silicone additive (BYK-UV3530), and 50 parts by weight of methyl ethyl ketone were mixed using a stirrer and then filtered using a PP filter to prepare a first hard coating composition.
[0137] Examples and Comparative Examples: Production of Hard Coating Films
[0138] The hard coating compositions of the above-mentioned Production Examples 1 to 12 were laminated in the order described in the following Table 1 and Table 2 to produce hard coating films.
[0139] Specifically, to form the first hard coating layer, the composition of each manufacturing example was applied 40 times on a 50 μm thin glass by a bar coater, and then the solvent was dried at 90° C. for 2 minutes. The dried coating film was irradiated with 600 mJ / cm 2 UV light was irradiated with a light intensity of 100 μm, thereby forming a first hard coating layer (HC1) of 25 μm. The composition of the manufacturing example corresponding to the embodiment was applied on the first hard coating layer formed above, thereby forming a second hard coating layer (HC2). For the composition of each embodiment, the second hard coating composition was applied 12 times using a rod coater, and the solvent was dried at 90°C for 2 minutes. Nitrogen was purged through the dried coating film, and the coating film was treated with nitrogen at 600 mJ / cm 2 The second hard coating layer was formed by irradiating with UV light at a light intensity of 7 μm, thereby manufacturing the final laminated hard coating film.
[0140] In the case of Comparative Example 6, the composition of Preparation Example 1 of the second hard coating layer was coated three times with a bar coater, and then the solvent was dried at 90° C. for 2 minutes. Nitrogen was purged through the dried coating film, and the coating film was heated at 600 mJ / cm 2 The second hard coating layer was formed by irradiating with UV light at a light intensity of 1 μm, thereby manufacturing the final laminated hard coating film.
[0141] In the case of Comparative Example 7, the composition of Preparation Example 1 of the second hard coating layer was coated 25 times with a bar coater, and then the solvent was dried at 90° C. for 2 minutes. Nitrogen was purged through the dried coating film, and the coating film was heated at 600 mJ / cm 2 The second hard coating layer was formed to have a thickness of 20 μm by irradiating with UV light at a light intensity of 100 μm, thereby manufacturing a final laminated hard coating film.
[0142] [Table 1]
[0143]
[0144]
[0145] [Table 2]
[0146]
[0147]
[0148] Experimental example
[0149] The physical properties of the hard coating films produced in Examples 1 to 9 and Comparative Examples 1 to 7 were measured by the following methods. The results are shown in Tables 1 and 2.
[0150] (1) Transmittance evaluation
[0151] The transmittance of the coating film was measured using a haze meter HM-150N manufactured by Murakami Co., Ltd.
[0152] (2) Scratch resistance evaluation
[0153] After the substrate film and the glass were bonded together with a transparent adhesive with the hard coating facing upward, steel wool (#0000) was used to rub the glass at a speed of 500 g / cm 2 The scratch resistance was measured by reciprocating rubbing 10 times with a load of 1.50 g.
[0154] <Evaluation Criteria>
[0155] ○: When the measurement portion was observed by transmission and reflection using a three-wavelength lamp, no scratches were observed or 10 or less scratches were observed.
[0156] X: When the measurement portion is observed by transmission and reflection using a three-wavelength lamp, more than 10 scratches are observed.
[0157] (3) Pencil hardness evaluation
[0158] After fixing the substrate film to the glass with the hard coating facing upward, the pencil hardness was measured under a load of 1 kg. The test was performed 5 times with a pencil of the same hardness at a length of 1 cm, and the hardness that passed 4 or more times was marked as the pencil hardness.
[0159] (4) Antifouling evaluation
[0160] The contact angle of water was measured using a contact angle meter DSA100 from KRUSS. The droplet volume was set to 3 μl at room temperature. A water contact angle of 110° or more was considered a pass standard for the contact angle.
[0161] (5) Wear resistance evaluation
[0162] The test was conducted using a wear tester from Dacheng Precision Co., Ltd. The contact angle was measured after the coating surface was wiped 3,000 times with a wear test eraser and a 500g weight. At this time, a water contact angle of 95° or more was considered acceptable for wear resistance.
[0163] (6) Chemical resistance evaluation
[0164] The test was carried out by the wear test equipment of Dacheng Precision Co., Ltd. The contact angle was measured after wiping the coating surface 3000 times with a wear test eraser and a 500g weight. Ethanol (purity 99.8%) was applied to the wiped sample every 50 times. At this time, the water contact angle of 95° or more was defined as the qualified standard for chemical resistance.
[0165] (7) Evaluation of POGO's compression resistance
[0166] After the hard-coated glass produced above was fixed with an adhesive (25 μm), the surface pressing performance was evaluated using a POGO pressing device.
[0167] After pressing the hard coating surface with a 5 mm POGO tip at 4 kg, the film was left to stand at 25° C. and 50% ambient conditions for 24 hours, and then the visibility of the pressed position was confirmed.
[0168] <Evaluation Criteria>
[0169] ○: 4kg is not visible
[0170] X: 4kg visible
[0171] (8) Evaluation of anti-scattering properties
[0172] The hard-coated glass prepared above was bent in a state where the opposite surfaces were bonded with an adhesive (25 μm) and compressed using a universal testing machine (UTM) until it broke.
[0173] The state of the hard coating surface of the broken sample was checked to confirm whether the broken glass fragments fell off the hard coating surface or whether there were separated fragments.
[0174] <Evaluation Criteria>
[0175] ○: No glass fragments were found
[0176] X: Glass fragments confirmed
[0177] (9) Adhesion evaluation
[0178] After the base film and glass were bonded with a transparent adhesive with the hard coating facing upward, 100 squares were cut horizontally and vertically at 1 mm intervals on the hard coating surface with a cutter, and then the adhesion test was performed three times with Mickybond tape.
[0179] The results are expressed as "the number of quadrilaterals that passed the tightness test / 100".
[0180] <Evaluation Criteria>
[0181] ○:100 / 100
[0182] X: 0~99 / 100
[0183] (10) Vickers hardness test
[0184] The sample was placed with the first hard coating layer facing upward, and the Vickers hardness of the first hard coating layer against compression was measured using a nano indenter (Fisher) at a micro load of 5 mN.
[0185] (11) Bendability evaluation
[0186] The hard coating film produced as described above was placed so that the second hard coating layers were in contact with each other, and was repeatedly folded 200,000 times so that the radius of curvature of the folded portion was 5 mm to perform a test.
[0187] <Evaluation Criteria>
[0188] ○: No cracks or breaks
[0189] X: Cracks or breaks
[0190] Referring to the experimental data in Tables 1 and 2 above, in the case of Examples 1 to 9 of the laminated bodies of the embodiments of the present invention, the pencil hardness is 3H or more, and excellent results are shown in the evaluation of scratch resistance, antifouling, wear resistance, chemical resistance, pressure resistance, anti-scattering, adhesion and bendability, while the hard coating layer deviates from one or more of the evaluation criteria of scratch resistance, antifouling, wear resistance, chemical resistance, pressure resistance, anti-scattering, adhesion and bendability evaluation of Comparative Examples 1 to 7 of the embodiments of the present invention, which does not conform to the present invention and does not show physical properties suitable for use as a hard coating film for flexible displays. In particular, the Vickers hardness of the first hard coating layer is greater than 20kgf / mm 2In the case of Comparative Example 1, a pressing phenomenon was observed in the pressing resistance evaluation, and glass fragments were confirmed in the anti-scattering evaluation. In addition, in the case of Comparative Example 6, in which the thickness of the second hard coating layer was less than 3 μm, the contact angle of water was measured to be less than 95° in the abrasion resistance and chemical resistance evaluations, and in the case of Comparative Example 7, in which the thickness of the second hard coating layer was more than 15 μm, cracks or breaks occurred in the bendability evaluation.
[0191] Therefore, it was confirmed that the hard coating film of the present invention and the window and image display device using the same have excellent physical properties in terms of durability when repeatedly folded, and particularly have an anti-scattering effect when broken.
[0192] Industrial Applicability
[0193] The hard coating film of the present invention and the window and image display device using the same have a pencil hardness of 3H or above, and are excellent in scratch resistance, anti-fouling, wear resistance, chemical resistance, pressure resistance, anti-scattering, adhesion and bendability, and can improve device reliability when applied to flexible displays.
Claims
1. A hard coating film for forming on display glass, characterized in that: Include: A first hard coating layer comprising a silane or siloxane compound and having a Vickers hardness of 20 kgf / mm 2 The following; and The second hard coating layer is formed on the first hard coating layer, contains a compound containing a fluorine-based UV-curable functional group, and has a thickness of 3 to 15 μm.
2. The hard coating film according to claim 1, characterized in that The display glass is ultra-thin glass UTG.
3. The hard coating film according to claim 1, characterized in that The display glass, the first hard coating layer, and the second hard coating layer are each formed in direct contact without including an additional layer. 4 . The hard coating film according to claim 1 , wherein the compound containing a fluorine-based UV-curable functional group has 1 to 6 UV-curable functional groups. 5 . The hard coating film according to claim 1 , wherein any one of the first hard coating layer and the second hard coating layer is made of a composition containing one or more selected from the group consisting of a photopolymerizable compound, an initiator, and a solvent. The hard coating film according to claim 5 , wherein the photopolymerizable compound further comprises an inorganic nanofiller. 7 . The hard coating film according to claim 1 , wherein any one of the first hard coating layer and the second hard coating layer further comprises an additive. 8 . The hard coating film according to claim 7 , wherein the additive comprises at least one selected from the group consisting of a leveling agent, a UV stabilizer, and a heat stabilizer. 9 . The hard coating film according to claim 1 , which is applied to a flexible display.
10. A window comprising a display glass and a hard coating film formed on the display glass, The hard coating film includes the hard coating film according to any one of claims 1 to 9.
11. An image display device comprising the window according to claim 10.
Citation Information
Patent Citations
Transparent substrate
KR101408511B1